LIBERALISME DALAM PEMIKIRAN BELIA DI MEDIA SOSIAL (LIBERALISM THOUGHT AMONG YOUTH ON SOCIAL MEDIA) - Norsaleha Mohd. Salleh; Noor Hafizah Mohd. Haridi; Phayilah Zakaria; Juzlinda Mohd. Ghazali; Gazali Bin Runun Abdullah; Mohd. Shairawi Mohd. Noor (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
ABSTRACTThis study aims to identify liberalism thought among youth on social media. The liberalism influence was identified through the sharing of views and thoughts of the youth at risk on their social media account in the form of comments or writings uploaded. The study was conducted through a month of focussed observation on eleven youth at risk who were inclined towards promoting liberalism thought on the social media. The youth were selected based on the active share of their views on issues pertaining to Islam and the active status update via personal social media such as Twitter, Facebook, and page. The findings showed that three out of eleven youth uploaded an average of five to twelve statuses a day. Meanwhile, seven out of eleven youth uploaded statuses based on season and issues that occur at a time. The study also found that they have a network that helps them in terms of giving moral support or offering views that support one another and being vocal towards current issues especially the ones involving the Islamic Shariah, Shariah court and religious authority in Malaysia. The study contributes current reality for the nation’s policymaker to prepare guidelines for the use of social media among youth.